Dispotition Effect And Momentum - Dea Nurita (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background - An important challenge for behavioral finance is to find a direct relationship between the behavior of individual investors and asset price dynamics. One of irrational investors are most conspicuous in the financial markets is the tendency of some investors to sell winner stocks too early and keep losers stocks too long, called the disposition effect. Disposition effect can trigger a momentum in the stock price. Aim - To examine the past returns and disposition effect in predicting the momentum of stock returns. Desaign / methodology / approach - The data used in this study is weekly data. This study uses a variable capital gain overhang as a proxy disposition effect. Other variables used in this study is the stock return short, medium, and long period, turnover short, medium, and long period, and market capitalization. The analytical method used is regression and different test. Results and Discussion - Simultaneous test results also show that the variables of short period return, medium period return, long period return, short period turnover, medium period turnover, long period turnover, and market capitalization together have an effect on the capital gain overhang variable. The adjusted R2 value in this model shows that the independent variable in this equation is able to explain the dependent variable of 35.1%. Stocks with a low capital gain overhang (G1), have a low return value as well. Likewise, stocks with high capital gain overhangs (G4), have high return values. The disposition effect is an important cause of momentum, stocks with high capital gain overhangs will have positive returns. From these results, it can be concluded that hypothesis 2 is supported, namely the disposition effect can predict the presence of momentum in stock returns. Conclussion - The results showed past returns can predict the momentum in stock returns and disposition effect could predict the momentum of stock return. Research Implication –This research can provide an overview of the anomalies that often occur in the capital market, particularly the existence of the disposition effect and momentum in the Indonesian capital market. Limitations – This research uses only one proxy, namely the capital gain overhang as a proxy for the disposition effect which was first developed by the research of Grinblatt and Han (2005) and there are no other proxies that can be used to compare research results